Penerapan (Sop) Standard Operating Procedure Dalam Meningkatkan Pelayanan Room Service di Hotel Bali Niksoma Boutique Beach Resort - Saputra, Gede Wira; Nugraha, I Gede Putra (Universitas Pendidikan Ganesha, 2025)
This study is a qualitative descriptive research that aims to identify and evaluate the application of Standard Operating Procedure (SOP) in room service services at Hotel Bali Niksoma Boutique Beach Resort. The discussion of the research leads to an explanation related to the implementation of standard operating procedures (SOP) in improving the quality of room service, the obstacles faced and the strategies used by Bali Niksoma Boutique Beach Resort to maintain service quality and guest loyalty. This research was conducted for 4 months with a qualitative descriptive method with data collection techniques in the form of observation, in-depth interviews, and document studies. This research interview was conducted with two people, the first with the Assistant Restaurant Outlet Manager, the second with Bali Niksoma Boutique Beach Resort employees, and used standard operating procedure documents (SOP) to set service quality standards. The results of this study show that the implementation of optimal standard operating procedures (SOP), careful planning, clear organization or division of labor, fast and precise implementation, and operational supervision are strategies used to improve the quality of room service, guest satisfaction and guest loyalty.